Econometric Analysis Regarding the use of Labor Resources at the Level of Romania - Florina BRAN; Laurentiu COROBAN; Victor Marian DUMITRACHE; Oana Camelia IACOB PARGARU (Revista de Management Comparat International)
The labor market is a market with imperfect competition, which must present a certain flexibility that leads to greater competitiveness and systematically and favorably influences economic growth. In the current conditions of the market economy, the social division of labor is deepening considerably, the workforce being structured by age, sex, socio-professional categories, qualification levels, geographical areas and employment opportunities. depending on the performance parameters, the main labor market characterized by high levels of stability and safety and the secondary labor market characterized by parameters specific to the periphery of economic activity can be delimited. Also, the labor market can be analyzed as the labor market characteristic of the macroeconomic level and the labor market characteristic of the microeconomic level.